Pengaruh Kompetensi Profesional Guru Matematika Terhadap Prestasi dengan Motivasi dan Kemandirian Belajar Sebagai Variabel Intervening: Penelitian - Arie Setiawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to ascertain whether there is an indirect effect of professional competence of mathematics teachers on achievement through interveving variables; ascertain whether there is an effect of teacher professional competence on motivation and self-regulated learning. The research method used in this study is a survey method with a quantitative approach. The population in this study were all junior high school mathematics teachers in Jambi City with a sample of 54 teachers consisting of 63% civil servant teachers and 37% non-civil servant teachers, and 300 student respondents. The results of this study found that there was no significant influence between the professional competence of mathematics teachers on student learning achievement. The path coefficient value of 0.2% which is positive indicates that the higher the professional competence of mathematics teachers, the higher the student learning achievement. The intervening variable does not provide an influence in the relationship between the professional competence of mathematics teachers on student learning achievement. This shows that there is no significant difference between the direct effect of teacher professional competence on learning achievement and the indirect effect through other variables, namely motivation and self-regulated learning.